The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/nyas.13859
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of music‐based rhythmic auditory cueing in Parkinson's disease

Abstract: Gait dysfunctions in Parkinson's disease can be partly relieved by rhythmic auditory cueing. This consists in asking patients to walk with a rhythmic auditory stimulus such as a metronome or music. The effect on gait is visible immediately in terms of increased speed and stride length. Moreover, training programs based on rhythmic cueing can have long-term benefits. The effect of rhythmic cueing, however, varies from one patient to the other. Patients' response to the stimulation may depend on rhythmic abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 71 publications
1
51
0
5
Order By: Relevance
“…To differentiate these types, a recent study investigated if healthy subjects synchronized their steps to music when uninstructed and instructed, and concluded that instruction was required for synchronization to occur. 11 This finding is consistent with previous studies in healthy controls (HCs) and in persons with PD 12,13 as well. Yet, in these studies, the motor thresholds where participants were asked to walk was set at either 5%, 10%, 13 and 10%, 15% 11 above or below their usual walking frequency.…”
Section: Introductionsupporting
confidence: 92%
“…To differentiate these types, a recent study investigated if healthy subjects synchronized their steps to music when uninstructed and instructed, and concluded that instruction was required for synchronization to occur. 11 This finding is consistent with previous studies in healthy controls (HCs) and in persons with PD 12,13 as well. Yet, in these studies, the motor thresholds where participants were asked to walk was set at either 5%, 10%, 13 and 10%, 15% 11 above or below their usual walking frequency.…”
Section: Introductionsupporting
confidence: 92%
“…Also, we only observed enhanced power at the beat frequency following beat-based sequences in about half of the participants, in line with individual differences in reliance on beat-based perception. Understanding individual differences in temporal expectations is therefore an important direction for future research, with significant implications for applications of musical rhythm, such as in motor rehabilitation (Dalla Bella, Dotov, Bardy, & Cochen De Cock, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sonification efficiently reduced the variability of golf swing gestures in novices 118,119 , or improved the pedal force effectiveness among cyclists 120 . The beneficial effects of sonification in reeducating patients with severe gait dysfunctions, such as Parkinson's disease patients, by rhythmic auditory cueing [21][22][23]121 , or neuromotor deficits related to the fluency of handwriting, such as dysgraphia [122][123][124][125][126] , were also well recognized. In the same way, we suppose that such continuous auditory feedback may help musicians and dancers improve or recover their body awareness, for example, through experiments of sound tracing and motor mimicry, which are already known to stimulate covert mental images associated with musical experience 58,81,127,128 .…”
Section: Discussionmentioning
confidence: 99%
“…In dance practice, conversely, the mirror neuron system may decode the perceived expressiveness into fine movement structures through the same kind of grounded synergetic processes [16][17][18] . In the domain of rehabilitation, rhythmic auditory stimuli were efficient in reducing movement disorders and improving walking abilities in Parkinson's disease and stroke patients [19][20][21][22][23] .…”
Section: Jocelyn Rozé * Mitsuko Aramaki Richard Kronland-martinet mentioning
confidence: 99%